Globalisation and equality - Patapan, Haig.; Horton, Keith (New York : Routledge, 2004)
"Is globalisation creating a more unequal world? Is it creating new forms of inequality? Does it make certain pre-existing forms of inequality more morally or politically significant than they would otherwise have been? Globalisation and equality examines these and related questions, exploring the way increasing globalisation is challenging our conceptions of equality. The contributors explore these themes from both theoretical and empirical perspectives. Some adopt a more abstract approach, exploring foundational questions concerning the meaning of equality, its social and political dimensions, and more specifically its moral implications in a global context. Others engage the general themes of globalisation and equality by focusing on specific topics, such as welfare, citizenship, gender, culture and the environment. Original in the questions it poses, and interdisciplinary in its approach, this collection of essays will appeal to all those with an interest in globalisation and equality"--P. [4] of cover.
Includes bibliographical references and index.
Keywords: Equality; Globalization